Functional trait effects on ecosystem stability: assembling the jigsaw puzzle. (September 2021) - de Bello, Francesco; Lavorel, Sandra; Hallett, Lauren M.; Valencia, Enrique; Garnier, Eric; Roscher, Christiane; Conti, Luisa; Galland, Thomas; Goberna, Marta; Májeková, Maria; Montesinos-Navarro, Alicia; Pausas, Juli G.; et al.
Abstract : Under global change, how biological diversity and ecosystem services are maintained in time is a fundamental question. Ecologists have long argued about multiple mechanisms by which local biodiversity might control the temporal stability of ecosystem properties. Accumulating theories and empirical evidence suggest that, together with different population and community parameters, these mechanisms largely operate through differences in functional traits among organisms. We review potential trait-stability mechanisms together with underlying tests and associated metrics. We identify various trait-based components, each accounting for different stability mechanisms, that contribute to buffering, or propagating, the effect of environmental fluctuations on ecosystem functioning. This comprehensive picture, obtained by combining different puzzle pieces of trait-stability effects, will guide future empirical and modeling investigations. Highlights: The main mechanisms by which biodiversity affects the stability of ecosystem functions (dominant species, compensatory dynamics, and insurance effects) all act through the functional traits of organisms that form local communities. These mechanisms can be assessed using different components of trait value distributions within and between species [collectively referred as trait probability density (TPD)]. Variation in local populations can result in overall changes in community structure, which may or may not be propagated into changes in ecosystem functions. The extent of such propagation depends on: (i) the extent of TPD shifts, and (ii) the overlap between response and effect traits, and these effects will vary depending on the biotic mechanisms being assessed.